1998
DOI: 10.1002/(sici)1521-4109(199810)10:14<976::aid-elan976>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

A Cathodic Stripping Square-Wave Voltammetry of a Second-Order Redox Reaction and Its Application to the Mercury-Cysteine System

Abstract: A model of cathodic stripping square-wave voltammetry of a second-order redox reaction is developed. Both reversible and quasireversible redox reactions are considered. The relationships between the properties of SWV response and both parameters of the redox reaction and the SWV excitation signal are analyzed. The effect of the concentration of the reacting ligand on the SW voltammograms is discussed. The phenomenon of a quasireversible maximum is demonstrated. Numerical simulations are compared qualitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In our previous publication [14] we demonstrated that which appear at more negative and more positive potentials, respectively) does not depend significantly on the SW amplitude and its average value is 0.9490.04.…”
Section: Resultsmentioning
confidence: 70%
“…In our previous publication [14] we demonstrated that which appear at more negative and more positive potentials, respectively) does not depend significantly on the SW amplitude and its average value is 0.9490.04.…”
Section: Resultsmentioning
confidence: 70%
“…The latter mechanism is known as the cathodic stripping reaction of second order [12]. Numerous inorganic ions, such as halides [13 ± 17], cyanide [18], thiosulfate and sulfite [19] as well as some of the sulfur containing organic compounds, such as miscellaneous thiols [20 ± 25] and thioamides [26] react according to the Reaction II.…”
Section: Hg (L) L 2àmentioning
confidence: 99%
“…In the present paper, utilizing the recently developed theoretical models [11,12,33,34] a comparative analysis of all four electrode mechanisms under conditions of SWV is presented. The aim of the study is to establish simple diagnostic criteria for qualitative recognizing and distinguishing the type of the cathodic stripping reaction.…”
Section: Hg (L) L 2àmentioning
confidence: 99%
“…The scientific interest for the theoretical examination of the cathodic stripping processes has significantly raised in the recent years [4, 5, 12 ± 15]. Thus, we have recently studied theoretically the cathodic stripping process of second order (Reaction II) [14] as well as the cathodic stripping reaction of first order coupled by adsorption of the reacting ligand (Reaction III) [4].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is of particular interest, since many organic compounds reacting as monovalent ligands are capable to adsorb on the electrode surface [3,14]. The aim of this work is to investigate the relationships between the properties of the SW voltammetric response and both the redox kinetic parameters and parameters of the excitation signal.…”
Section: Introductionmentioning
confidence: 99%